Pengaruh Kinerja Front Office Department Terhadap Kepuasan Tamu di Hotel Grand Arkenso Parkview Semarang - Alamsyah, Muhammad Chairul; Aprilliyani, Renny (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This research aims to evaluate the direct impact of Front Office Department performance on guest satisfaction. The research method used is a quantitative method with regression analysis. This research sample involved 232 respondents who were hotel guests who stayed at the hotel during the research period. Data was collected through a questionnaire that focused on guest perceptions of FOD performance and satisfaction levels.Research confirms that the performance of the Front Office Department has a significant effect on guest satisfaction. From the regression analysis, a positive relationship can be seen between performance and guest satisfaction with the regression equation Y = 13,047 + 0.570(X). The F test showed statistical significance (F = 109.830, p < 0.05), and the Coefficient of Multiple Determination (R2) of 56.8% indicated that most of the variation in guest satisfaction could be explained by performance. Reliability results confirm the consistency and reliability of the data.The conclusion is that performance has a crucial role in increasing guest satisfaction at the Grand Arkenso Parkview Hotel Semarang. Factors such as efficiency of the check-in/check-out process, friendliness of staff, handling of complaints and accuracy of information appear to have a significant impact. These findings provide in-depth insight into improving services to achieve higher guest satisfaction, which can ultimately strengthen guest loyalty and the hotel's image in the market. It also provides a basis for future service improvements and technology implementation